Assessing the Feasibility and Challenges of CRISPR-Cas9 for Treating Genetic Disorders - Maria Fernández; Valmore Madriñan; Palacio Santiago; Andrés Bermudez (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
This study explores the potential applications of CRISPR-Cas9 technology in treating genetic disorders in Colombia, with a specific focus on thalassemia and sickle cell anemia, which disproportionately affect Afro-Colombians. Given the country’s rich genetic diversity, which includes Afro-Colombians, mestizos, and indigenous populations, the study examines how CRISPR could be tailored to address region-specific genetic mutations and improve health outcomes. The objective of this research is to assess the feasibility, challenges, and strategic implications of CRISPR for genetic disorders in Colombia, considering factors such as healthcare infrastructure, social resistance, and genetic variation. The methodology employed includes a comprehensive review of existing literature, comparative analysis of global CRISPR applications, and a synthesis of data from genetic studies specific to Colombia’s population. The findings indicate that while CRISPR offers significant promise for addressing genetic diseases, challenges such as healthcare accessibility, high costs, and the country’s genetic diversity must be overcome. Furthermore, ethical concerns regarding genetic modification must be addressed through public education and engagement. Future research should focus on expanding genetic databases, particularly for underrepresented populations, and exploring the economic and social implications of CRISPR therapies in Colombia's rural and marginalized communities. These efforts will help ensure that CRISPR technology is effectively and equitably applied to improve public health outcomes.